Learning English From a Critical, Intercultural Perspective: The Journey of Preservice Language Teachers - Claudia Patricia Gutiérrez (Universidad Nacional de Colombia, 2022)
Critical language teaching education has become an inescapable endeavor for language teacher education programs. To contribute to this effort, this paper outlines the implementation of an English course from a critical, intercultural perspective, during the first semester of a language teacher education program in Colombia. It also reports the ways preservice teachers responded to this implementation as evidenced in data stemming from their oral and written outcomes and from course evaluations. Results indicate that this approach to language teaching allowed preservice teachers to affirm their multiple identities as they developed and strengthened their language skills in English. Data also indicate that looking at the world from a more critical perspective entailed contradictions and challenges for preservice teachers and the teacher educator.